Nét Huế trong các ca từ về Huế/Võ Xuân Hào - Võ,Xuân Hào
Hue is well-known for not only as an ancient capital of the Nguyen Dynasty but also as an attractive is tourist place for poetry, arts and songs. Hue is said to be one of the most interesting cities in Vietnam remaining unique ancient features, is an endless romantic inspiriting source for lots compositors, poets, and artists coming from different parts of our country and foreign ones. Hue’s Sonatas have thrilled both: Hue people and those who have never been to Hue. Hue keeps inside many track prints expressed in poetry, arts and songs, but above all of these, the lyrics songs about Hue. The romantic, deeply thoughtful lyrics of bring to itself its unique features. Nowhere else in this country there have been the same characteristics as those in Hue, and may be of that the lyrics of the songs are so gentle, deeply thoughtful, picturesque, wet of rain.